Assessment of fracture resistances of endodontically treated teeth filled with different root canal filling systems - Padma Chandra; Vishal Singh; Shelly Singh; Govind Nandkumar Agrawal; Amit Heda; Nikita Sureshkumar Patel (Wolters Kluwer Medknow Publications, 2021)
Background: The motive of endodontic therapy is cleaning, shaping, and subsequently obturation. This study assessed different root canal filling systems in terms of fracture resistances of endodontically treated teeth. Methodology: This study was conducted on eighty single-rooted permanent mandibular incisor teeth which were divided into five groups: Group I was negative control; Group II was positive control; Group III comprised of gutta-percha/AH Plus; Group IV comprised of Thermafil/AH Plus; and Group V Resilon/Epiphany SE. Universal testing machine measured fracture resistance. Results: The mean fracture resistance in Group I was 458.6 ± 112.4 N, in Group II was 214.8 ± 104.6 N, in Group III was 428.6 ± 108.2 N, in Group IV was 388.2 ± 126.2 N, and in Group V was 334.8 ± 102.7 N. The difference found to be statistically significant (P < 0.05). Intergroup comparison showed a statistically significant difference (P < 0.05) between Groups I-II, I-V, II-III, and II-IV. Conclusion: The authors found that lateral condensation performed with AH Plus sealer and gutta-percha and the Thermafil technique were the highest among all other methods.